The Organic Turn: Coping With Pandemic and Non-pandemic Challenges by Integrating Evidence-, Theory-, Experience-, and Context-Based Knowledge in Advising Health Policy - Pfaff, Holger; Schmitt, Jochen (Frontiers in Public Health, 2021)
The COVID-19 pandemic is an extraordinary challenge for public health and health policy. From a systemic coping perspective, questions concerning the main strategies to cope with this situation and the lessons to be learned from these strategies arise. This conceptual paper aimed to clarify these questions by using sociological concepts. Concerning the coping strategy questions, we see a strong tendency in health policy to rely on expert knowledge rather than on evidence-based knowledge. The evidence-based healthcare community reacts to this and responds to urgent demands for advice by processing new knowledge rapidly. Despite these attempts, makers of health policy still mainly rely on experts. Our sociological analysis of this situation led to three lessons learned to cope with pandemic and non-pandemic health challenges, namely (1) the phenomenon of accelerating knowledge processing could be interpreted from the organizational innovation perspective as a shift from traditional mechanistic knowledge processing to more organic forms. The first lesson learned is that this “organic turn” should be the first choice in fast-moving areas in health sciences in the future; (2) the return of the experts is part of this organic turn and shows that experts provide “ideal” evidence-based knowledge plus additional helpful knowledge components. The second lesson learned is that these additional components – theoretical, experiential and context knowledge – should be integrated with evidence-based knowledge and, in sum, lead to knowledge-based health policy advice; (3) Experts can use theory to provide advice expeditiously in times when there is limited evidence available and provide orientation in times where knowledge production leads to an overload of knowledge. Therefore, the third lesson learned is that evidence-based knowledge should be complemented by theory-based knowledge in a structured two-way interaction to obtain the most comprehensive and valid recommendations for knowledge-based health policy from science, in both unstable situations such as pandemics and in more stable times.